Flow cytometric analysis of Ca2+-induced changes of membrane potential in smooth muscles mitochondria - Babich, Lidia; Shlykov, Sergiy; Naumova (Kandaurova), Natalia; Kosterin, Sergiy (My University, 2008)
A flow cytometric protocol for the analysis of membrane potential and Са2+ level in isolated myometrium mitochondria was developed. Ca2+ addition induced the mitochondrial membrane depolarization. At the presence of Mg2+ and ATP, the Ca2+ addition did not cause the membrane potential dissipation. It was demonstrated that the flow cytometry is a useful tool to analyze Са2+ level and membrane potential in isolated myometrium mitochondria.
Keywords: flow cytometry; проточна цитометрія; проточная цитометрия; isolated mitochondria; mitochondrial membrane potential; ізольовані мітохондрії; мембранний потенціал мітохондрій; изолированные митохондрии; мембранный потенциал митохондрий